METODE PENGUKURAN PADA EVALUASI KONDISI BANGUNAN BERSEJARAH TERHADAP KEMIRINGAN ATAU PERBEDAAN ELEVASI (STUDI KASUS MASJID JAMI KESULTANAN SAMBAS) - Vita Ilona Wijaya; Zairin Zain; Yudi Purnomo (JMARS: Jurnal Mosaik Arsitektur, 2022)
According to the Law of the Republic of Indonesia Number 11 of 2010, the forms of cultural heritage are very diverse and one of them is in the form of buildings. Sambas is one of the areas that have a long-standing cultural heritage building, namely the Jami Mosque of the Sambas Sultanate. This building has been standing since 1727 and is one of the witnesses to the history of the sultanate government in Sambas in the past. The age of the mosque is now more than 100 years and attention to the condition of the building is needed, especially to the slope or difference in elevation. Therefore, this study was conducted to evaluate the condition of the historic building of the Jami Mosque of the Sultanate of Sambas on the slope or difference in elevation. This research was conducted by quantitative descriptive with field observation data collection methods and literature review. Field observations were carried out through manual measurements. The measurement data will be processed to evaluate its condition. Measurements will be carried out on one of the rooms in the Jami Mosque of the Sambas Sultanate, namely the Storage Room. From the results of measurements of the floor of the Storage Room, the results showed that there was a deflection of the floor at one of the measuring points. This can indicate a slope, so further inspection is needed to determine the factors causing the slope, as well as recommendations for improvement to minimize the risk of the slope getting worse.